Evalusai Efektivitas Penggunaan Media Pembelajaran dengan Wordwall Dalam Keterlibatan dan Pemahaman Siswa - Rosyid, Farhan; Alwi, Nur Azmi (Cerdas Proklamator, 2024)
This research aims to evaluate the effectiveness of using Wordwall learning media in improving student engagement and understanding. Using a qualitative approach with Systematic Literature Review (SLR) method, this research analyzes various recent research articles about Wordwall implementation in learning. The analysis results show that the use of Wordwall significantly improves student learning outcomes, as indicated by the increase in learning outcome percentages. This platform proves to be effective in enhancing learning motivation. Wordwall implementation also contributes to increasing student learning interest. This research concludes that Wordwall is an effective interactive learning media in creating an enjoyable learning atmosphere, increasing student engagement, and supporting the understanding of learning materials. However, its successful implementation depends on teachers' readiness in managing the classroom and designing appropriate learning activities. Recommendations for future research include exploring Wordwall's effectiveness in developing higher-order thinking skills and students' collaborative abilities.